Harmonization of Levy System in Customary Village Referred to Mineral Mining Transporting Activity - Lestari, Putu Ulandari Sri; Kartika, I Gusti Ayu Putri (SASI, 2023)
Introduction: The uncertainty surrounding levies on mineral mining transportation activities requires an observation of the legal concepts that have conceptualized the levies and the system that is being used. Therefore, there is a need for harmonization of the levy concept related to indigenous villages.Purposes of the Research: This study is aimed to determine the boundaries of authority of the Customary Village towards the implementation of state authority and the levy category for the mineral mining transportation.Methods of the Research: This study uses a normative research method because the legal issues discussed are related to the implementation of statutory norms, namely the Regional Regulations on Traditional Villages in Bali with higher statutory regulations, through a conceptual approach, as well as the snowball technique used in collecting legal materials with the technique such as descriptions, comparisons, evaluations, and arguments in analyzing legal materials.Results of the Research: The authority of the indigenous village to regulate the levies collected by the indigenous village as long as they do not conflict with higher regulations is considered valid. The concept of levies regulated in legislation classified as specific levies, as the object is the transportation of mineral mining, is not collected by force but voluntarily regarding the tariff amount, and has been agreed upon in the form of awig-awig (a social norm regulation of Balinese society) and can be categorized as a valid levy, as the levies imposed are not separated from the elements of Tri Hita Karana.